LEGAL, ORGANIZATIONAL AND ECONOMIC ASPECTS OF PHYSICAL REHABILITATION AND REINTEGRATION OF COMBAT VETERANS - Pantielieieva N.M.; Rogova N.V.; Braichenko S.M.; Kletsenko L.V.; Dzholos S.V. (Scientific Journal of Pedagogy and Economics, 2020)
The article analyzes the best practices of foreign experience of rehabilitation services for war veterans. The modern institutional structure, legal and organizational aspects of the rehabilitation and reintegration of war veterans are characterized. The essence, importance and necessity of physical rehabilitation, the creation of a single rehabilitation space, the introduction of an interactive map for the provision of social rehabilitation services in accordance with uniform standards, as well as systems for monitoring their effectiveness and quality at the state level, are substantiated. It is concluded that the success of rehabilitation and re-adaptation programs for war veterans depend on the timely adoption of necessary legal acts, proper financing, and rational use of budget funds. It is emphasized the importance to strengthen the economic mechanism for the rehabilitation and reintegration of war veterans on the basis of principles - targeting, diversification, adaptation to the socio-economic profile of each war veteran and the domestic economic situation in the country, maximally activating new forms of cooperation and partnerships between government bodies, non-governmental organizations and business. It is concluded that national systems of rehabilitation and reintegration of war veterans require a paradigm shift in accordance with modern international approaches, standards and practices.